2023
DOI: 10.1111/obr.13658
|View full text |Cite
|
Sign up to set email alerts
|

Weight regain, body composition, and metabolic responses to weight loss in weight cycling athletes: A systematic review and meta‐analyses

Sarah Bagot,
Léna Pélissier,
Bruno Pereira
et al.

Abstract: Depending on the nature of their sports, athletes may be engaged in successive weight loss (WL) and regain, conducing to “weight cycling.” The aims of this paper were to systematically (and meta‐analytically when possible) analyze the post‐WL recovery of (i) body weight and (ii) fat mass; fat‐free mass; and performance and metabolic responses in weight cycling athletes (18–55 years old, body mass index < 30 kg.m−2). MEDLINE, Embase, and SPORTDiscus databases were explored. The quality and risk of bias of th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 194 publications
0
1
0
Order By: Relevance
“…Studies based on athletes from different sports have observed that sequential weight loss and recovery alters body expression and metabolism. However, compared to non-athletic normal-weight individuals, weight cycling athletes may not have excess fat, and the main reason for this phenomenon is that athletes do not just rely on diets to lose weight [ 87 ].…”
Section: Strategy For Weight Cycling Controlmentioning
confidence: 99%
“…Studies based on athletes from different sports have observed that sequential weight loss and recovery alters body expression and metabolism. However, compared to non-athletic normal-weight individuals, weight cycling athletes may not have excess fat, and the main reason for this phenomenon is that athletes do not just rely on diets to lose weight [ 87 ].…”
Section: Strategy For Weight Cycling Controlmentioning
confidence: 99%